La música en la educación primaria y en las escuelas de música: La necesaria coordinación - Maravillas Díaz (Ediciones Complutense, 2004)
The research herein focuses on the study and the analysis of music education in primary schools and schools of music in the Autonomous Basque Region. Based on the analysis and understanding of the situation in the schools, it elaborates joint action proposals to support and enhance music education, in order to bring children of six to twelve years old the possibility of enjoying making music according to their abilities.